3D carbon networks and their polymer composites: Fabrication and electromechanical investigations of neat Aerographite and Aerographite-based PNCs under compressive load. (January 2017) - Garlof, Svenja; Mecklenburg, Matthias; Smazna, Daria; Mishra, Yogendra Kumar; Adelung, Rainer; Schulte, Karl; Fiedler, Bodo
Abstract: Aerographite is a lightweight 3D nanocarbon network which offers covalent interconnections for polymer nanocomposites (PNCs). Here, the electrical and mechanical properties of neat Aerographite and Aerographite-based PNCs are investigated in detail. The Aerographite filler networks consist of hollow, graphitic tubes of μm-sized diameters and nm-sized wall thicknesses. Different densities of Aerographite in the range of 0.6–13.9 mg/cm 3 have been investigated towards their mechanical deformation behavior, electrical conductivities and piezoresistive response under compression. This basic characterization of filler networks is compared to resulting PNCs if the Aerographite is fully embedded in epoxy matrix. It can be shown that the use of 3D interconnected Aerographite results in high electrical conductivities at low filler contents, e.g., 2–8.7 S/m for weight fractions of 0.1–1.2 wt.-%. The neat Aerographite has been characterized in detail by scanning electron microscopy (SEM), X-ray diffraction (XRD) and Raman spectroscopy techniques. To explain the observed piezoresistive behavior of these 3D nanocarbon-based PNCs, a qualitative micromechanical model is introduced. The model describes the internal graphitic wall slippage and loss of interconnections of the inner electrically conductive networks under load. The piezoresistive response of Aerographite-based PNCs can be directly correlated to the applied outer mechanical loads. Graphical abstract: